2018
DOI: 10.1186/s12889-018-5725-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a diabetes prevention program for rural women with prior gestational diabetes mellitus: study protocol of a multi-site randomized clinical trial

Abstract: BackgroundIn China, about 53.4 million women (11%) have type 2 diabetes (T2DM). Women with prior 2 (GDM) are at a high risk for T2DM. Postpartum lifestyle interventions have been effective in reducing T2DM for this population, but the evidence is limited to interventions provided in urban areas, despite the fact that a higher prevalence of undiagnosed T2DM was found in rural areas in China. The primary purpose of this proposed study is to examine the effect of a postpartum intensive lifestyle modification (ILS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
(14 reference statements)
0
23
0
Order By: Relevance
“…The baseline survey was carried out among a sample of 465 rural, nondiabetic, nonpregnant women with a history of GDM, from two geographical areas in rural Hunan, China, in 2017. The selection process for the setting and participants was described in our previous study [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The baseline survey was carried out among a sample of 465 rural, nondiabetic, nonpregnant women with a history of GDM, from two geographical areas in rural Hunan, China, in 2017. The selection process for the setting and participants was described in our previous study [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The multisite randomized clinical trial (RCT) has been reported elsewhere and registered in the Chinese Clinical Trial Registry (ChiCTR) (No. ChiCTR1800015023) [ 24 ]. To represent different socioeconomic status, lifestyle, and ethnic groups in the Hunan Province, two counties were selected as study sites: one county with a less developed economy and a large ethnic minority population and another county with middle to high economic development and a predominately Han population.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size of n = 320 (160 in the intervention group and 160 in the control group) was based on the change in insulin resistance in a previous trial [ 24 ]. For testing hypotheses about the impact of the intervention on QoL measures, we calculated power based on the G*Power 3 option “ANOVA repeated measures for between group (2 groups) by within group (3 times) interactions” based on F-tests [ 24 ]. The null hypothesis is that this interaction is nil and the alternate hypothesis is that the intervention group will show more positive change than the control group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is a baseline survey on the dietary practice of women with a history of GDM. This work is part of a randomized clinical trial (ChiCTR1800015023) that aims to examine the effect of intensive lifestyle modifications on physiological health outcomes (e.g., T2DM development, insulin resistance, and weight-related variables) for women with previous GDM in rural areas [ 18 ]. According to a previous study that applied CHEI to the 2011 China Health and Nutrition Survey, which obtained standard deviations (SDs) of 9.5 among rural residents and 11.3 among female participants [ 12 ], we calculated a sample size of 423 under a hypothesized SD of 10.0, allowance error of 1.0, and drop-out rate of 10% (PASS software version 11.0 for Windows, NCSS LLC, Kaysville, UT, USA).…”
Section: Methodsmentioning
confidence: 99%